Reconstructing Mediation Regulation in Contemporary Islamic Family Disputes: Reform Urgency in Indonesian Religious Courts - Putra Pandu Dinata Nurdiansyah; Lalu Muhammad Tamimi; Erfaniah Zuhriah; Naufal Rifqi Nasution (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Purpose - This study examines the urgency of reforming mediation regulations in Islamic family law disputes in Indonesian religious courts to be more responsive, in line with Islamic values and contemporary legal needs. The current mediation framework is often criticized for its rigidity, legal uncertainty, and procedural inefficiency, which hinder the timely resolution of disputes and limit access to justice. Methods - This study uses a normative legal research method with a legislative approach analysis. Primary and secondary legal materials were collected using a document study method, and these legal materials were then grouped and analyzed according to the formulation of each issue. Findings - The research identifies major regulatory shortcomings, including the weak enforceability of mediated agreements, inadequate mediator qualifications, and the absence of institutional support to encourage mediation. These issues contribute to prolonged litigation and discourage parties from choosing mediation. Reform is needed to establish a more flexible, transparent, and enforceable mediation system that upholds both procedural justice and Islamic legal principles. Research Limitations: This study is limited by its focus on analyzing regulations related to mediation that apply in Indonesia. Originality/Value: The study offers a conceptual framework for reconstructing mediation regulation by bridging Islamic jurisprudence with modern legal mechanisms.